2017
DOI: 10.1103/physrevlett.119.084101
|View full text |Cite
|
Sign up to set email alerts
|

Stable Chimeras and Independently Synchronizable Clusters

Abstract: Cluster synchronization is a phenomenon in which a network self-organizes into a pattern of synchronized sets. It has been shown that diverse patterns of stable cluster synchronization can be captured by symmetries of the network. Here we establish a theoretical basis to divide an arbitrary pattern of symmetry clusters into independently synchronizable cluster sets, in which the synchronization stability of the individual clusters in each set is decoupled from that in all the other sets. Using this framework, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 37 publications
1
97
0
Order By: Relevance
“…Remark 1: (Network symmetries, equitable partitions, and balanced weights) Conditions to ensure the invariance of the cluster synchronization manifold have been linked to network symmetries, which are defined by the group comprising all node permutations that leave the network topology unchanged, e.g., see [31], [32], [44]. In Fig.…”
Section: Problem Setup and Preliminary Notionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 1: (Network symmetries, equitable partitions, and balanced weights) Conditions to ensure the invariance of the cluster synchronization manifold have been linked to network symmetries, which are defined by the group comprising all node permutations that leave the network topology unchanged, e.g., see [31], [32], [44]. In Fig.…”
Section: Problem Setup and Preliminary Notionsmentioning
confidence: 99%
“…Invariance of exact cluster synchronization, which is the notion used in this paper, is also studied in [41], [42]. Stability of exact cluster synchronization is investigated in [43] where, however, only the restrictive case of two clusters for identical Kuramoto oscillators with inertia is considered, and in [44], where only implicit and numerical stability conditions are provided. To the best of our knowledge, our work presents the first explicit analytical conditions for the (local) stability of the cluster synchronization manifold in sparse and weighted networks of heterogeneous Kuramoto oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…For finite-size systems, some chimera states have been shown to be long transients [38], while others have been shown to be stable [39,40] using the Watanabe-Strogatz ansatz [41,42]. Recent research has placed increased emphasis on chimeras in finite-size networks of chaotic oscillators [43][44][45][46][47], which are important given the prevalence of chaos in physical systems [48]. In that context, it has been shown that the stability of chimera states can be studied rigorously using cluster synchronization techniques [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has placed increased emphasis on chimeras in finite-size networks of chaotic oscillators [43][44][45][46][47], which are important given the prevalence of chaos in physical systems [48]. In that context, it has been shown that the stability of chimera states can be studied rigorously using cluster synchronization techniques [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidences from large-size complex network possessing permutation symmetries have been also provided [43][44][45][46][47][48]. With the help of computational group theory algorithm [50], the permutation symmetries of large-size complex networks now can be identified numerically, which, combining with the generalized method of eigenvalue analysis [44,46,49,51,52], can be used to analyze the formation of cluster synchronization in the general complex networks.…”
Section: Introductionmentioning
confidence: 99%